2007
DOI: 10.1086/519815
|View full text |Cite
|
Sign up to set email alerts
|

Did Reform of Prudent Trust Investment Laws Change Trust Portfolio Allocation?

Abstract: This paper investigates the effect of changes in state prudent trust investment laws on asset allocation in noncommercial trusts. The old prudent-man rule favored "safe" investments and disfavored "speculation" in stock. The new prudent-investor rule directs trustees to craft an investment portfolio that fits the risk tolerance of the beneficiaries and the purpose of the trust. Using stateand institution-level panel data from 1986-97, we find that after adoption of the new prudent-investor rule, institutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
2
17
1
Order By: Relevance
“…Historically, a “prudent man” (PM) standard of fiduciary care caused some institutional investors to avoid holding shares that did not pay cash dividends. The PM standard judged the appropriateness of each security position on a stand‐alone basis, and the payment of regular dividends became a “safe harbor” indicator of a stock's “prudence.” The literature contains clear evidence that the PM standard caused bank trust departments to shun non‐dividend‐paying stocks (Del Guercio, 1996; Schanzenbach and Sitkoff, 2007). Moreover, PM restrictions probably had effects far beyond their narrow applicability to trusts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, a “prudent man” (PM) standard of fiduciary care caused some institutional investors to avoid holding shares that did not pay cash dividends. The PM standard judged the appropriateness of each security position on a stand‐alone basis, and the payment of regular dividends became a “safe harbor” indicator of a stock's “prudence.” The literature contains clear evidence that the PM standard caused bank trust departments to shun non‐dividend‐paying stocks (Del Guercio, 1996; Schanzenbach and Sitkoff, 2007). Moreover, PM restrictions probably had effects far beyond their narrow applicability to trusts.…”
mentioning
confidence: 99%
“…Differences between the location of the fiduciary and the beneficiary raised the possibility that a suit might be brought under either state's laws. Schanzenbach and Sitkoff (2007) studied the impact of PI adoption on trust companies operating in the state that changed its law. They argued that such trusts are clearly subject to their home state's fiduciary standards, assuming implicitly that all their trust assets belong to trusts established in the same state.…”
mentioning
confidence: 99%
“…In Schanzenbach and Sitkoff (), we examined trust asset allocation between 1986 and 1997. We found that after a state's adoption of the prudent investor rule, institutional trustees held about 2 to 4 percentage points more stock than before, predominately at the expense of government bonds and other investments deemed “safe” by prior law .…”
Section: Trust Investment Law Economics and Financementioning
confidence: 99%
“…Whether trustees have applied the law properly in practice, however, has yet to be studied. The importance of this question is highlighted by the fact that since adoption of the rule, stockholdings in personal trusts have increased substantially at the expense of government bonds, partly in response to the rule (Schanzenbach & Sitkoff ). Against this backdrop of movement outward on the risk/return curve, we examine how the rule has affected management of market risk by trustees.…”
Section: Introductionmentioning
confidence: 99%
“…In legal terms, a trust is a fiduciary relationship in which the trustee holds legal title to specified property, entrusted to him by the settlor, and manages that property for the benefit of one or more beneficiaries (Schanzenbach and Sitkoff ). Since the purpose of the trust is often to supply reliable source of income to the surviving spouse and children, who have low tolerance for risk, and not to maximize the value of the trust corpus, risk management is more important than value maximization.…”
mentioning
confidence: 99%